خداع الذات و علاقته بالرفاهية النفسية لدى طلبة جامعة صلاح الدين-أربيل - عزيز, ‌‌أ.د. عمر ابراهيم; محمد, م.م. خندان صابر (Sulaimani Journal for Humanities, 2023)
The current study aimed to identify the level of self-deception and psychological well-being among university students. In addition, identify the correlation between self-deception and psychological well-being and the ability of areas of self-deception to predict psychological well-being. Identify the significance of differences for self-deception and psychological well-being according to the gender variable. The number of members of the research sample reached (400) students of the faculties of Salahaddin University, (160) males and (240) females. To measure self-deception, the researchers built a scale to measure self-deception and the psychometric properties of the scale were extracted using factor analysis and the scale consisted of (29) items and consists of four components that are manipulation of information, sense of control, justification, overconfidence. To measure psychological well-being, the Ryff scale (1989), (42) items, that consists of (6) areas, namely independence, personal growth, environmental growth, positive relationships, life goal, self-acceptance. Levels of self-deception among the members of the research sample and recording high levels of psychological well-being. The existence of a negative relationship between self-deception and psychological well-being. Gender and the stage of study are a good predictor in the relationship of self-deception with psychological well-being. The domains of manipulation and overconfidence of the self-deception variable are also good predictors of psychological well-being. The results also indicated that there are significant differences according to the gender variable for the self-deception variable and for the areas of manipulation and justification in favor of males. There are statistically significant differences according to gender for the areas of positive relationships with others, goal in life, self-acceptance and in favor of Female. In the light of the results, the researchers made a number of recommendations and to develop the current research, the researchers made a number of proposals.
Keywords: selfdeception; psychological wellbeing; university students